Intergenerational Solidarity in Post- Industrial Societies: Sosiological Persfektives - Wijaya, Wijaya; Sianipar, Godlif; Yuna, Jung; Parera, Dishan (Cognitionis Civitatis et Politicae, 2025)
Intergenerational solidarity has become a critical issue in post-industrial societies where demographic shifts, such as aging populations and declining birth rates, are reshaping social structures. The traditional bonds between younger and older generations are being challenged by economic, technological, and cultural transformations. Understanding how these changes impact intergenerational relationships is essential for maintaining social cohesion and addressing the needs of diverse age groups. Despite its importance, there is limited research on how post-industrial dynamics affect intergenerational solidarity. This study aims to explore the sociological dimensions of intergenerational solidarity in post-industrial societies. The research focuses on understanding how economic pressures, technological advancements, and shifting cultural norms influence the relationships between different generations. By examining these factors, the study seeks to provide a deeper understanding of the mechanisms that support or weaken intergenerational bonds in contemporary society. A qualitative research design was employed, utilizing in-depth interviews with individuals from various age groups, as well as focus group discussions. The study also incorporates secondary data analysis of demographic and socioeconomic trends in post-industrial countries. The data were analyzed using thematic coding to identify key patterns and factors influencing intergenerational solidarity. The findings reveal that while economic and technological changes pose challenges to intergenerational relationships, strong cultural and familial values continue to play a vital role in maintaining solidarity. The study concludes that fostering intergenerational solidarity requires policy interventions that address these disparities while promoting mutual understanding and support between generations.